2018
DOI: 10.1155/2018/8694397
|View full text |Cite
|
Sign up to set email alerts
|

Using the Spleen as anIn VivoSystemic Immune Barometer Alongside Osteosarcoma Disease Progression and Immunotherapy withα-PD-L1

Abstract: Indications for immunotherapies are still unclear, and there is a great need for real-time patient immune status monitoring. In this study, we confirmed that the local and systemic immune profiles of an orthotopic osteosarcoma model with or without luciferase transfection were statistically equivalent. Next, we used flow cytometry to describe systemic immune cell populations influenced by osteosarcoma disease progression. When compared to vehicle-inoculated sham mice, it was found that tumor-bearing mice had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…The progression and metastasis of osteosarcoma may induce an imbalance of macrophage subtype populations ( 36 ). It was reported that M2-like macrophage marker molecules, including CD206, Arg-1, and Ym-1, were significantly upregulated in the osteosarcoma tissues compared with non-tumor tissues ( 37 ).…”
Section: Macrophages and Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…The progression and metastasis of osteosarcoma may induce an imbalance of macrophage subtype populations ( 36 ). It was reported that M2-like macrophage marker molecules, including CD206, Arg-1, and Ym-1, were significantly upregulated in the osteosarcoma tissues compared with non-tumor tissues ( 37 ).…”
Section: Macrophages and Osteosarcomamentioning
confidence: 99%
“…Similarly, it has been reported that anti-PD-L1 treatment blocks the PD-L1 signaling pathway, promoting macrophage proliferation and activation, leading to pro-inflammatory macrophage phenotypes ( 141 ). In an osteosarcoma mice model, the PD-L1 inhibitor also promoted monocyte maturation and returned macrophage M1/M2 marker expression to nearly normal status ( 36 ).…”
Section: Macrophages and Osteosarcomamentioning
confidence: 99%
“…The association between the host immune system, the type of cancer and cancer treatment applied is extremely complex (29,30). Immunotherapies that include PD-1/PD-L1 blockade have shown prolonged clinical activity against various human malignancies excluding OS (31), despite the fact that there is evidence that PD-L1 contributes to OS progression in animal experiments (32). As the main components of the innate immune system, NK cells can kill tumor cells or infected cells directly, independent of antigen presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing reverse transcription-quantitative polymerase chain reaction (RT-qPCR), PD-L1 mRNA expression was determined to be associated with lymphocyte infiltration (31). PD-L1 blockade in a mouse model of OS revealed the initial regression of the tumor followed by growth of PD-L1 antibody-resistant clones (32). PD-L1 expression was significantly linked to poor 5-year survival rates (33).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in the TME and immunity against a tumor are not just confined to the tumor, and/or the tumor‐draining lymph nodes, but can cause systemic immune dysfunction. In this light, a study of osteosarcoma found that T cells in the spleen of tumor‐bearing mice showed an exhaustion status [28]. In addition, there was an increase in the percent populations of Tregs and MDSCs in the spleens of the tumor‐bearing mice.…”
Section: Systemic Changes Mediated By Tumor Cellsmentioning
confidence: 99%